India after Naxalbari : unfinished history - D'Mello, Bernard (Monthly Review Press, 2018)
"Political and sociological analysis of the Naxalite movement, beginning with its 1967 armed peasant uprising in Naxalbari, at the foot of the Indian Himalayas, and continuing into the present as the world's longest-running revolutionary "people's war," based in Maoist resistance."--Provided by publisher.